Pengaruh Organisasi Terhadap Fokus Belajar Mahasiswa Pendidikan Sosiologi UNM - Nurul Anggraeni; Yulianti Eni; M. Ridwan Said Ahmad; M. Syukur; Ibrahim Arifin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Organizations are one of the most frequently carried out activities by students in developing their interests and talents. Not only that, organizations can also train leadership, increase insight, improve communication skills, and so on. However, this is actually a debate among students because they think that the organization will disrupt their study focus. This should be a concern for students as to how the organization can have a good impact, including on the focus of student learning.